ANALISIS YURIDIS PEMBIAYAAN MUDHARABAH DENGAN JAMINAN KEBENDAAN PADA PERBANKAN SYARIAH MENURUT HUKUM ISLAM (STUDI PADA BANK SYARIAH MANDIRI CABANG KOTA LHOKSEUMAWE) - DEWI EKA SAPUTRI (PREMISE LAW JURNAL, 2016)
Mudharabah financing is a mandate and trust financing. It is not allowed to ask for collateral to the managers because it is merely the capital manager. The problems of the research were how about the implementation of mudharabah financing in Bank Syariah Mandiri, Lhoksemawe Branch Office in accordance with the Islamic Law, how about the implementation of collateral in the mudharabah financing in Bank Syariah Mandiri, Lhoksemawe Branch Office according to the Islamic Law, and how about the role of a notary related to the collateral binding in the mudharabah financing by Bank Syariah Mandiri, Lhoksemawe Branch Office. In order to give answers to these problems, the research used empirical judicial approach with qualitative descriptive method which analyzed the primary, secondary, and tertiary data, and conducted interviews. The result of the research shows that is, Mudharabah financing is principally done without any collateral from the customers, however, in practice, the Bank still request for collateral from the fund manager in order to prevent any deviance by the manager so that it reduces the risk over the payment. The implementation of the collateral in practice is based on two grounds, namely to secure stockholders’ trust on the agency and the society’s situation and condition today which have been altered in regard of commitment to the noble values, such as trust and honesty. Keywords : Mudharabah Agreement, Collateral, Sharia Bank